ANALISIS PRAXEOLOGY: PENGENALAN KONSEP NILAI DAN ARAH VEKTOR PADA BUKU PAKET KELAS X SMA - Brata, Syahrizal Kurniawan; Nurjanah, Nurjanah; Suryadi, Didi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
The concept of vectors in mathematics is defined as a quantity that has a value and direction. Students' interpretation of the concept of vector value and direction becomes a problem because of the adjustment of the sources of understanding used by students in learning. This study aims to analyze the introduction of the concept of vector value and direction in mathematics textbooks. A mathematics textbook for grade X high school in the independent curriculum was reviewed using the theory of praxeology. The analysis process was carried out in three main stages, namely the examination of the praxis block, analysis of the logos block, and evaluation of the structure of the praxis textbook. The test results showed that there were problems in the praxis block, namely the presentation of unclear visual data and the problem of the sequence of material in the logos block and learning was only limited to one context. The results can explore the potential for ontogenic obstacles, namely in the praxis block and the potential for didactic and epistemological obstacles in the logos block. The findings in this study indicate the need for improvements to textbooks.